2023
DOI: 10.3390/ma16155494
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Performance of Sol-Gel Prepared TiO2 Thin Films Annealed at Various Temperatures

Lu He,
Dietrich R. T. Zahn,
Teresa I. Madeira

Abstract: Titanium dioxide (TiO2) in the form of thin films has attracted enormous attention for photocatalysis. It combines the fundamental properties of TiO2 as a large bandgap semiconductor with the advantage of thin films, making it competitive with TiO2 powders for recycling and maintenance in photocatalytic applications. There are many aspects affecting the photocatalytic performance of thin film structures, such as the nanocrystalline size, surface morphology, and phase composition. However, the quantification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…To improve the photocatalytic ability of TiO 2 , researchers have attempted changing the forbidden bandwidth of TiO 2 [2], annealing to change the type of TiO 2 crystalline phase [3], doping to form defects [4], creating composite thin films [5], and modifying the surface [6]. Among them, the crystalline phase transformation of TiO 2 due to changing the annealing temperature (T a ) has been widely studied because of its crucial importance in the photocatalytic process [7]. Albetran and Low showed that TiO 2 transforms from an amorphous to an anatase phase when annealed at 600 • C and to a rutile phase when annealed at 700 • C [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the photocatalytic ability of TiO 2 , researchers have attempted changing the forbidden bandwidth of TiO 2 [2], annealing to change the type of TiO 2 crystalline phase [3], doping to form defects [4], creating composite thin films [5], and modifying the surface [6]. Among them, the crystalline phase transformation of TiO 2 due to changing the annealing temperature (T a ) has been widely studied because of its crucial importance in the photocatalytic process [7]. Albetran and Low showed that TiO 2 transforms from an amorphous to an anatase phase when annealed at 600 • C and to a rutile phase when annealed at 700 • C [8].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al showed that rutile crystalline phases also possess photocatalytic ability [13]. The crystalline phase transformation, crystalline size, and photocatalytic changes of TiO 2 during the annealing process are also different for TiO 2 prepared by different preparation methods [7,[14][15][16]. Therefore, a comparison of the physical structural, optical, and photocatalytic properties of TiO 2 thin films prepared by different preparation methods during the annealing process needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%